Avaliação da resposta ao tratamento do enfisema pulmonar grave através da medida de densidades pulmonares obtidas pela tomografia computadorizada de tórax após implante de válvulas endobrônquicas: série de casos - Thaís Mesquita Ferreira (2023)
Introduction: Pulmonary hyperinflation is one of the main consequences of severe pulmonary emphysema, leading to exercise intolerance in patients due to changes in ventilatory mechanics. High-resolution chest computed tomography (HRCT) has been used as the preferred method for quantifying pulmonary emphysema through measurements of lung densities. Objective: To assess the response to treatment with unidirectional endobronchial valves in patients with severe heterogeneous pulmonary emphysema, using pulmonary densitometry measurements by high-resolution chest computed tomography (HRCT). Methodology: Patients were evaluated with a complete pulmonary function test, high-resolution chest computed tomography (HRCT), and dyspnea scoring using the mMRC scale before the procedure and three to six months after EBV implantation. The quantification of pulmonary emphysema was performed by measuring densities on HRCT with thresholds of -950 Hounsfield units (HU) and -910 HU. Continuous variables were analyzed using the one-tailed paired Wilcoxon signed-rank test or one-tailed paired t-test when appropriate, with a significance level of p < 0.05 considered significant. Results: Ten patients were analyzed, and a significant reduction in pulmonary emphysema volume was observed after the implantation of unidirectional endobronchial valves (EBV), both for the -950 Hounsfield unit (HU) densities (667 ml; p=0.006) and the -910 HU densities (454 ml; p < 0.001). Additionally, there was an improvement in dyspnea severity assessed by the mMRC scale (1.6 points; p=0.008). Moreover, a notable correlation was found between pulmonary deflation and an increase in inspiratory capacity (CI) (p=0.0064), and a correlation between an increase in CI and a reduction in the mMRC dyspnea grade (p=0.0456). However, there was no isolated improvement in the analyzed pulmonary function variables. Conclusion: HRCT, with analysis of pulmonary densities, can be an effective tool in evaluating the degree of pulmonary deflation achieved with the implantation of unidirectional endobronchial valves (EBV) in patients with severe and heterogeneous pulmonary emphysema.